2009
DOI: 10.1007/s10979-008-9145-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of the SIRS in compensation cases: An examination of its validity and generalizability.

Abstract: The Structured Interview of Reported Symptoms (SIRS; Rogers et al., Structured interview of reported symptoms (SIRS) and professional manual, 1992) is a well-validated psychological measure for the assessment of feigned mental disorders (FMD) in clinical, forensic, and correctional settings. Comparatively little work has evaluated its usefulness in compensation and disability contexts. The present study examined SIRS data from 569 individuals undergoing forensic neuropsychiatric examinations for the purposes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
(40 reference statements)
1
29
0
Order By: Relevance
“…Psychological tests such as the MMPI-2 and the SIRS have proven to possess highly accurate classification rates (Tolin et al, 2010;Rogers et al 2009a), whereas an individual clinician's classification accuracy has almost never been subject to scientific study. Additionally, we know that in general actuarial judgment outperforms clinical judgment (Dawes, Faust, & Meehl, 1989).…”
Section: Accurate As Medical Testsmentioning
confidence: 99%
“…Psychological tests such as the MMPI-2 and the SIRS have proven to possess highly accurate classification rates (Tolin et al, 2010;Rogers et al 2009a), whereas an individual clinician's classification accuracy has almost never been subject to scientific study. Additionally, we know that in general actuarial judgment outperforms clinical judgment (Dawes, Faust, & Meehl, 1989).…”
Section: Accurate As Medical Testsmentioning
confidence: 99%
“…The SIRS is a structured interview to detect malingering and related problematic response styles in psychiatric/ psychological evaluations. Rogers et al ( 2009 ) have reported results supporting its use in compensation and disability settings. Morel ( 2010 ) did not cite research on its use for malingered PTSD.…”
Section: Morel (2010)mentioning
confidence: 96%
“…The ATR of the TSI should be used cautiously . For the SIRS, according to Rogers et al ( 2009 ), it does not detect very well PTSD symptom over-reporting, although research is ongoing. The MENT appears to be a useful adjunct for malingering detection.…”
Section: Rosen and Grunert (2012)mentioning
confidence: 99%
See 2 more Smart Citations